Experimental investigation of the near-bit jet pump - Kryzhanivskyi, Ye. I.; Panevnyk, D. O. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
The nature of the flow distribution in the hydraulic system of the near-bit jet pump has been analyzed. The peculiarities of searching the pumping station operating point have been shown and the equation for determining hydraulic losses in the elements of the ejection system has been given. Based on experimental studies, an error in the theoretical determination of the relative pressure of a jet pump has been established when using a known and advanced model of its working process. In contrast to the known method, the proposed model provides for the determination of the hydraulic resistance of the chisel flushing system, which is located in the area of mixed flow at the cost of working, not mixed flow. Improving the mathematical model of the ejection system allows to reduce the error of theoretical determination of the relative pressure of the jet pump.